PADMA PANJALU JAYATI MOTIF TENUN IKAT BASED ON THE RELIEFS OF THE KEDIRI KINGDOM TEMPLE - Frans Aditia Wiguna; Erwin Putera Permana (Universitas Pendidikan Ganesha, 2020)
Woven cloth is made diverse in various regions in the archipelago, especially in Java Island, where each region has its own uniqueness and special characteristics in terms of motif and colors. the Difference be caused by location geographical, beliefs, customs and the surrounding natural conditions including flora and fauna, each region has certain differences and uniqueness as well as contacts or relationships between regions. “Its history can be observed from the batik motif itself, including painting of plants, animals and stories of antiquity” (Prasetyo, 2010:28). Design is a framework of form or design and motif are a style (Indonesian Dictionary, 1990:200). The stage of analyzing the main problem in this study is the weaving model/ weaving design/ weaving motif with the reliefs of the legacy temples of Kediri Kingdom, this study was reviewed qualitatively. To find out the dynamics of ikat waving design in Kediri, the problem formulation is how do weaving models in Kediri by applying designs/ motifs from temple reliefs? Culture can be observed from two points of view. First, limiting culture from an artistic point of view (temple relief). Second, are looking for a new motif model for Kediri weaving.